Impact of Bronchiectasis on COPD Exacerbations - Antonio Molino; Carolina Vitale; Tullio Valente; Maria D’Amato; Mauro Mormile; Pasquale Imitazione; Angelantonio Maglio; Alessandro Vatrella (International Journal of Thorax, 2018)
The presence of bronchiectasis is considered an aggravating factor in COPD patients. In particular, the coexistence of bronchiectasis and COPD was associated with greater frequency and severity of exacerbations. The aim of this study is to investigate the impact of bronchiectasis in patients with COPD exacerbation. We retrospectively collected data from 212 patients admitted to the hospital with diagnosis of COPD exacerbation. In order to detect the presence of bronchiectasis, only patients that had received a chest HRCT scan examination were included in the study. We compared clinical and functional data between COPD patients with bronchiectasis and those without bronchiectasis. The prevalence of bronchiectasis was 31,6% in this study. The presence of bronchiectasis in COPD patients was associated with increased risk for isolation of PPMs in the airway (56,1% vs 28,3%, p 0,02), and in particular of Pseudomonas Aeruginosa (17,5% vs 5,6% p 0,02), and with a longer duration of hospitalization (8,22 ±3,67 vs 6,88 ± 3,43 days, p=0.004). These results could encourage efforts to optimize medical care for patients with COPD and bronchiectasis. Clinical trials with treatments for infective component are needed to investigate their impact on the reductions of exacerbations and improvements in the disease course.
Keywords: COPD